A4_1 Hammer Down! - Tzabach, Lee Eliyahu; Birch, Hannah; Savic, Natasha (Physics Special Topics, 2023)
In this paper, we investigate the properties of Reinhardt’s Rocket Hammer from the video game Overwatch. We model the hammer with three V2 rocket engines powering the swing instead, and find the thrust force and thus velocity the hammer would be travelling at by the ends of one swing. We find the total thrust Ttotal = 959.7 kN, and the hammer velocity vhammer = 1161ms−1